Edexcel AS and A level Further Mathematics Core Pure Mathematics Book 1/AS Textbook. (2017) - Attwood, Greg; Bettison, Ian; Barraclough, Jack; Goldberg, David; Macpherson, Alistair; Moran, Bronwen; Nicholson, Su; Pateman, Laurence; Petran, Joe; Pledger, Keith; Staley, Geoff; Wilkins, Dave; et al.
No abstract available